Self-rated health and risk of incident essential tremor: A prospective, population-based study (NEDICES) - Benito-León, Julián; Louis, Elan D.; Villarejo-Galende, Alberto; Labiano-Fontcuberta, Andrés; Bermejo-Pareja, Félix (Parkinsonism & related disorders, 2015)
Essential tremor (ET), a highly-prevalent, progressive, aging-associated neurological disease, poses a significant public health challenge. Aside from its associated motor features, the disease affects cognition in some patients, mood, and morale, and has been associated with increased risk of mortality in the elderly. Studies have not investigated the relationship between self-rated health and risk of ET. We determined whether baseline poor self-rated health was associated with increased risk of incident ET. In this prospective, population-based study of people ≥65 years of age, subjects were evaluated at baseline and 3 years later. At baseline, subjects were asked to rate their health using a single-item health question. Hazard ratios (HR) of ET according to baseline self-rated health (very good, good, fair, poor, and very poor) were estimated with Cox models. The 3853 subjects had a median follow-up duration of 3.2 years. There were 82 incident ET cases. Compared to subjects who rated their health as good or very good, the risk of ET was increased for subjects who rated their health as fair (HR = 1.69, p = 0.03), and for subjects who rated their health as poor or very poor (HR = 2.12, p = 0.02). In a fully adjusted model, the risk remained increased for subjects who rated their health as poor or very poor (HR = 2.34, p = 0.01). Subjects rating their health as poor/very poor at baseline were at increased risk of incident ET at follow-up. Premotor and/or early motor symptoms of ET could negatively influence self-perceptions of health status. •Subjects rating their health as poor/very poor are at increased risk of incident essential tremor (ET).•Poor/very poor self-rated health is likely to be a marker of poor physical and mental health status, including ET.•Premotor symptoms of ET may negatively influence self-perceptions of health status.